2022
DOI: 10.3390/molecules27144425
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Inclusion Complexation of Fluconazole with Sulfonatocalix[4]naphthalene in Aqueous Solution, Solid-State, and Its Antimycotic Activity

Abstract: The study aims to assess the interaction between fluconazole and sulfonatocalix[4]naphthalene towards enhancing its dissolution performance and antimycotic activity. A solubility study was carried out at different pH conditions, and the results revealed the formation of a 1:1 molar ratio fluconazole-sulfonatocalix[4]naphthalene inclusion complex with an AL type phase solubility diagrams. The solid powder systems of fluconazole-sulfonatocalix[4]naphthalene were prepared using kneaded and co-evaporation techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Spray drying with sealed heating techniques of preparation resulted in improved complex formation in the case of α-CD, β-CD, and γ-CD, and kneading is found to be ineffectual, as stated by scientists who have examined the effect of α-CD, β-CD, and γ-CD on Ibuproxam. Chowdary and colleagues investigated the interaction of Nimesulide with β-CD and found that the kneading method resulted in more drug dissolution than coevaporation [26]. Palmieri et al found that for β -CD, HP β -CD, and Methoxybutyrate, the best complexation results were obtained via solid dispersion, kneading was unsuccessful, while spray-drying resulting in complete complexation with a fixed ratio of 1:4 [29].…”
Section: The Influence Of Preparation Techniquesmentioning
confidence: 99%
“…Spray drying with sealed heating techniques of preparation resulted in improved complex formation in the case of α-CD, β-CD, and γ-CD, and kneading is found to be ineffectual, as stated by scientists who have examined the effect of α-CD, β-CD, and γ-CD on Ibuproxam. Chowdary and colleagues investigated the interaction of Nimesulide with β-CD and found that the kneading method resulted in more drug dissolution than coevaporation [26]. Palmieri et al found that for β -CD, HP β -CD, and Methoxybutyrate, the best complexation results were obtained via solid dispersion, kneading was unsuccessful, while spray-drying resulting in complete complexation with a fixed ratio of 1:4 [29].…”
Section: The Influence Of Preparation Techniquesmentioning
confidence: 99%
“…15 The antimycotic activity showed substantial enhancement of FNL with FNL inclusion complex (FNL-IC) against Candida albicans and Candida glabratan strains. 16 Traditional ocular drug delivery systems used include topical formulations such as eye drops (solutions, suspensions, and emulsions), gels, ointments, and injections (including subconjunctival and intrascleral injections). 17 However, limitations associated with the topical application include drug washout through the nasolacrimal duct resulting in 80% of the drug not reaching the target, dilution in the tear fluid, drug metabolism, and drainage into the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that IC of FNL with SB-β-CD and hydroxypropyl-β-cyclodextrin can increase the bioavailability of the drug . The antimycotic activity showed substantial enhancement of FNL with FNL inclusion complex (FNL-IC) against Candida albicans and Candida glabratan strains …”
Section: Introductionmentioning
confidence: 99%